Reproductive outcomes of infertile couples undergoing assisted reproductive technology who are carriers of chromosomal abnormalities: a retrospective cohort study. (31st December 2022) - Cui, Ling; Wang, Fang; Lin, Yonghong; Li, Min
Abstract: Background: The aim of this study is to determine whether infertile couples who are carriers of chromosomal abnormalities have distinct cumulative clinical pregnancy and cumulative live birth rates among patients undergoing assisted reproductive technology (ART). Methods: Design: A retrospective cohort study. Setting: Department of Reproduction and Infertility in Chengdu Women's and Children's Central Hospital. Patients: A total of 112 couples were in the exposed group with chromosomal abnormalities, and 226 couples without chromosomal abnormalities were in the control group, totalling 338 cases enrolled from 1 January 2017 to 31 December 2020. The control group (infertile couples without chromosomal abnormalities) was 1:2 matched by female age, type of infertility (primary, secondary), and type of ART (IVF, ICSI, or IUI). The primary outcomes were cumulative clinical pregnancy rate and cumulative live birth rate. Results: The results indicated that chromosome abnormalities did not lead to significant differences in primary outcomes. The overall cumulative clinical pregnancy rate and cumulative live birth rate were not statistically different between the two groups (74.8% vs. 81.6%, p = .150) and (65.4% vs. 69.1%, p = .508). Further analysis revealed that there was also no significant difference in cumulative miscarriage rate between the two groups (13.9% vs. 20.3%, p = .213). Conclusions: There were no significant differences in the cumulative clinical pregnancy rate or cumulative live birth rate between infertile couples with or without chromosomal abnormalities. KEY MESSAGES: The prevalence of infertility is rising year by year worldwide. Carriers of chromosomal abnormalities undergoing ART have the similar cumulative clinical pregnancy rate or cumulative live birth rate. The data we analysed have a certain significance for clinical decision-making involving ART for couples with chromosomal abnormalities, and it provides a meaningful reference for patients and physicians in the selection of PGT.